Evaluating the Impact of Artificial Intelligence on Recruitment Practices Insights from HR Professionals and Case Studies - Preeti Singh (European Economic Letters (EEL), 2024)
The advent of Artificial Intelligence (AI) in recruitment practices has marked a significant shift in the Human Resources (HR) landscape, promising increased efficiency, unbiased decision-making, and access to a broader talent pool. This study aims to evaluate the multifaceted impact of AI on recruitment practices, drawing insights from a mixed-methods analysis that includes a survey of HR professionals and in-depth case studies of organizations that have integrated AI into their recruitment processes. A sample of 250 HR professionals across various industries provided quantitative data, while qualitative insights were gleaned from five case studies, representing diverse sectors and organization sizes. The findings reveal that AI adoption in recruitment enhances efficiency and candidate diversity but also raises concerns regarding data privacy, candidate experience, and the potential for algorithmic bias. Notably, the effectiveness of AI tools was contingent upon the organization's size, sector, and the sophistication of AI implementation. Furthermore, this study highlights a growing need for regulatory frameworks and ethical guidelines to navigate the challenges posed by AI in recruitment. The implications of these findings are significant for HR practitioners, policymakers, and scholars, as they underscore the need for a balanced approach to AI integration that maximizes its benefits while mitigating its risks. This research contributes to the emerging body of literature on AI in HR and offers practical recommendations for organizations looking to navigate the complexities of AI-driven recruitment.